Infrastructure how Support of Manufacturing Technology in the Context of Management Systems Requirements - Kurilovsky, Tadeas; Panda, Anton; Jurko, Jozef (Manufacturing Technology Journal, 2009)
Introduction into problems - The quality of the product, generally perceived as a measure of requirement completion, is determined by many factors. One of the main factors is the level of infrastructure. Many of the established management systems which are consistent with accepted standards involve provision and infrastructure maintenance as a requirement of these standards. Machinery and equipment maintenance neccessary for conformity achievement is pursued as one of the processes through management systems of quality, environment and occupation health and safety.
Keywords: Machine; equipment; infrastructure; maintenance; management systems